Microenvironment of organizations in the field of veterinary medicine - Дідок, Ю. В. (Scientific Progress & Innovations, 2015)
The article discusses the features of external environment of organizations in the field of veterinary medicine. The group of factors of direct influence were allocated and characterized. The definition of the notion «Microenvironment of establishments of veterinary medicine» was formulated and its essence was disclosed. Microenvironment of establishments of veterinary medicine should be understood as a complex of factors of direct impact, which directly affect the functioning of the organization in the field of veterinary medicine and they are exposed to their influence, they are able to determine the strategic decisions and to form a system of relations (connections) between the organization and its suppliers, competitors, consumers of veterinary goods and services, human resources, financial institutions, governmental authorities, civil society organizations and the media.